1700 MPa級超高力ボルトの大気腐食環境での遅れ破壊挙動 - 木村, 勇次; 山口, 隆司; 森山, 仁志; 長崎, 英二; 増田, 浩志; 津﨑, 兼彰 (Kou kouzou rombunshuu, 2025)
We have developed 1700 MPa-class ultra-high-strength bolts with a waisted shank and a new thread form to enhance tensile deformation capacity. This study evaluated the delayed fracture behavior of the developed bolts by an outdoor exposure test in Okinawa. Delayed fracture of the bolts became more pronounced when the fastening force increased from 391 kN to 445 kN. On the other hand, accelerated delayed fracture tests demonstrated that the new thread form was effective in enhancing the delayed fracture resistance. Based on the results of the exposure and accelerated delayed fracture tests, the ways to improve the delayed fracture resistance of the developed bolts were discussed.